Repeated Vessel Interactions and Climate- or Fishery-Driven Changes in Prey Density Limit Energy Acquisition by Foraging Blue Whales - Guilpin, Marie; Lesage, Véronique; McQuinn, Ian; Brosset, Pablo; Doniol-Valcroze, Thomas; Jeanniard-du-Dot, Tiphaine; Winkler, Gesche (Frontiers in Marine Science, 2020)
Blue whale survival and fitness are highly contingent on successful food intake during an intense feeding season. Factors affecting time spent at the surface or at depth in a prey patch are likely to alter foraging effort, net energy gain, and fitness. We specifically examined the energetic consequences of a demonstrated reduction in dive duration caused by vessel proximity, and of krill density reductions potentially resulting from krill exploitation or climate change. We estimated net energy gain over a simulated 10-h foraging bout under baseline conditions, and three scenarios, reflecting krill density reductions, vessel interactions of different amplitudes, and their combined effects. Generally, the magnitude of the effects increased with that of krill density reductions and duration of vessel proximity. They were also smaller when peak densities were more accessible, i.e., nearer to the surface. Effect size from a reduction in krill density on net energy gain were deemed small to moderate at 5% krill reduction, moderate to large at 10% reduction, and large at 25 and 50% reductions. Vessels reduced cumulated net energy gain by as much as 25% when in proximity for 3 of a 10-h daylight foraging period, and by up to 47–85% when continuously present for 10 h. The impacts of vessel proximity on net energy gain increased with their duration. They were more important when whales were precluded from reaching the most beneficial peak densities, and when these densities were located at deeper depths. When krill densities were decreased by 5% or more, disturbing foraging blue whales for 3 h could reduce their net energy gain by ≥ 30%. For this endangered western North Atlantic blue whale population, a decrease in net energy gain through an altered krill preyscape or repeated vessel interactions is of particular concern, as this species relies on a relatively short feeding season to accumulate energy reserves and to fuel reproduction. This study highlights the importance of distance limits during whale-watching operations to ensure efficient feeding, as well as the vulnerability of this specialist to fluctuations in krill densities.